Electrode of seawater hydrogen production electrolytic cell and preparation method thereof

By forming a molybdenum-containing catalyst layer on the electrode of the seawater hydrogen electrolytic cell, the problem of insufficiency of the catalyst and the substrate is solved, corrosion resistance and efficient catalysis of the electrode are achieved, and the service life of the electrode is extended.

CN119877011APending Publication Date: 2025-04-25SUZHOU JUNA NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840634.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-26
Filing Date
2024-10-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The electrodes of existing seawater hydrogen electrolytic cells have the problem of insolid bonding between the catalyst and the substrate, which leads to hindered charge transfer and insufficient exposure of catalyst active sites, which reduces catalyst activity and catalytic efficiency.

Method used

A catalyst layer with nanoparticles, nanowires, nanochains or nanosheet structures are prepared by forming a catalyst layer on the substrate by using materials such as metal precursor solutions, inducers, etc.

Benefits of technology

Effectively protect the electrode from chloride ion corrosion, extend the service life, improve the activity and catalytic efficiency of the catalyst, and enhance the performance of hydrogen production by electrolyzing water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877011A_ABST
    Figure CN119877011A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of seawater hydrogen production electrolytic cells, and particularly relates to an electrode of a seawater hydrogen production electrolytic cell and a preparation method of the electrode. And a catalyst layer, the surface of which comprises a metal or an oxidized metal of a molybdenum-based material. The preparation method at least comprises the following steps: providing a base material; and forming a catalyst layer on the substrate. According to the invention, the electrode can be protected from being corroded by chloride ions, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of seawater hydrogen production electrolyzers, and particularly relates to an electrode of a seawater hydrogen production electrolyzer and a preparation method thereof. Background Art

[0002] With the development of society, energy has gradually become a bottleneck restricting human development, and environmental problems have become increasingly prominent. Therefore, how to develop efficient and environmentally friendly renewable energy has become an important research topic for sustainable social and economic development. In recent years, people have gradually developed renewable energy sources such as solar energy, wind energy, and hydrogen energy. Among them, solar energy and wind energy are easily restricted by environmental factors, and their energy utilization efficiency is low and transportation is difficult. Hydrogen energy has the advantages of high calorific value, easy storage and transportation, and environmental protection and pollution-free, becoming the most promising energy in the 21st century.

[0003] At present, hydrogen production processes include water electrolysis, biomass combustion, coal gasification, solar photolysis, etc. However, the efficiency and cost of the catalyst still need to be further improved. Moreover, in the hydrogen production electrode, there are problems such as the weak bonding between the catalyst and the substrate, which in severe cases will hinder the transfer of charge, limit the full exposure of the catalyst active sites, reduce the catalyst activity and catalytic efficiency, and affect the performance of water electrolysis hydrogen production. Summary of the invention

[0004] To solve the above technical problems, the present invention is implemented through the following technical solutions.

[0005] The present invention provides an electrode for a seawater hydrogen production electrolyzer, characterized by comprising:

[0006] Base material;

[0007] The catalyst layer has a surface comprising a metal or metal oxide of a platinum-based material.

[0008] In one embodiment, the catalyst layer may include nanoparticles, nanowires, nanochains or nanosheet structures.

[0009] In one embodiment, the catalyst layer includes a first metal catalyst layer and a second metal catalyst layer, and the first metal catalyst layer and the second metal catalyst layer have different alloy ratios.

[0010] The present invention also provides a method for preparing an electrode of a seawater hydrogen production electrolyzer, which comprises at least the following steps:

[0011] providing a substrate;

[0012] A catalyst layer is formed on the substrate, wherein a surface of the catalyst layer includes a metal or an oxidized metal of a platinum-based material.

[0013] In one embodiment, the step of forming the catalyst layer comprises:

[0014] preparing a metal precursor solution;

[0015] Keep stirring at a preset temperature for a preset time to obtain an intermediate;

[0016] synthesizing the intermediate and nano-metal particles to obtain an electrode catalyst; and

[0017] The electrode catalyst is formed on the substrate.

[0018] In one embodiment, the metal precursor solution includes at least two of a transition metal, a lanthanide rare earth element, and a platinum group noble metal element, wherein the transition metal includes at least one of Mn, Cr, Zr, Fe, Co, Ni, Cu, Zn, Mo, or W, and the platinum group noble metal element includes at least one of Ru, Rh, Pd, Ag, Os, Ir, Pt, or Au.

[0019] In one embodiment, the preparation method further comprises:

[0020] A first inducer and a second inducer are added in sequence, wherein the first inducer includes solvents such as metal acid salts, metal halides, metal sulfates and metal nitrates, the metals are selected from at least two of Mn, Cr, Fe, Co, Ni, Cu, Zn and platinum group noble metal elements, and the second inducer is selected from at least one of organic solvents such as methanol, ethanol, propanol, acetone, dimethylformamide, cyclohexane, ethyl acetate and dimethyl sulfoxide.

[0021] In one embodiment, the (molar) ratio of the metal precursor solution, the first inducer and the second inducer is 1:1 to 1:10.

[0022] In one embodiment, the organic inducing agent in the electrode catalyst is selected from isophthalic acid esters, phthalates, 1,4-diazabicyclo[2.2.2]octane, triethylenediamine, 1,4-dimethylpiperazine, hexamethylenetetramine, pyromellitic acid, trimesic acid, 1,4-di(1H-pyrazol-4-yl)benzene, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracarboxylic acid, 2,4,6-tri(4-pyridyl)-1,3,5-triazine, tri(isobutylamino)- ... At least one of 2-(4-(4-ethyl)amine, bis(3,5-dicarboxyphenyl)azo, biphenyl dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-phenylenedicarboxylic acid, 1,1,2,2-tetra(4-carboxyphenyl)ethylene, 1,3,5-tri(4-carboxyphenyl)benzene, 2-(diphenylphosphino)terephthalic acid, 2-amino-4-hydroxy-6-methylpyrimidine, 2-methylimidazole, 2-aminoterephthalic acid, terephthalic acid, fumaric acid and trioctyl trimellitate.

[0023] In one embodiment, the catalyst layer includes a first metal catalyst layer and a second metal catalyst layer.

[0024] In summary, the present invention provides an electrode for a seawater hydrogen production electrolyzer and a preparation method thereof, which can protect the electrode from chloride ion corrosion and extend the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1-4 SEM images showing the structures of nanoparticles and nanoparticle clusters in electrode catalysts of different embodiments.

[0026] Figure 5 Shown is a schematic diagram of the microstructure of electrode catalysts in some embodiments of the present invention.

[0027] Figure 6 Shown are SEM images of electrode catalysts in some embodiments of the present invention.

[0028] Figure 7 Shown is a schematic diagram of the microstructure of electrode catalysts in some embodiments of the present invention.

[0029] Figure 8 Shown is a SEM image of the nanoparticles in the comparative example of the present invention.

[0030] Fig. 9 Schematic diagrams of nanoparticles of examples of the present invention and comparative examples are shown.

[0031] Fig.10 Shown is a SEM image of a high entropy nanoparticle cluster in an embodiment of the present invention.

[0032] Fig.11 Shown is a SEM image of conventional nanoparticles in a comparative example of the present invention.

[0033] Figure 12-14 Shown are scanning electron microscopy images of electrode catalysts in different examples.

[0034] Fig.15 Shows the actual image and performance curve of the membrane electrode prepared for electrode catalyst.

[0035] Figure 16-19 Shown are the shaped nanocatalysts in different embodiments.

[0036] Figure 20-21 Shown are scanning electron microscope images and X-ray energy spectrum images of the special-shaped nanocatalysts in different embodiments.

[0037] Fig. 22 The figure is a schematic flow chart of a method for preparing an electrode for producing hydrogen by electrolyzing water in one embodiment of the present invention.

[0038] Fig.23 It is a schematic diagram of analyzing the plating performance of electrochemical solution using Hastelloy plate when the concentration of the stabilizer is 10 g / L in one embodiment of the present invention.

[0039] Fig.24 It is a schematic diagram of analyzing the platability of electrochemical solution using Hastelloy film when the concentration of the stabilizer is 1.5 g / L in one embodiment of the present invention.

[0040] Fig.25 It is a schematic diagram of analyzing the platability of electrochemical solution using Hastelloy plate when the concentration of the stabilizer is 1 g / L in one embodiment of the present invention.

[0041] Fig.26 It is a schematic diagram of analyzing the plating performance of electrochemical solution using Hastelloy plate when the concentration of the stabilizer is 0.5 g / L in one embodiment of the present invention.

[0042] Fig. 27 This is a schematic diagram for analyzing the effect of the concentration of the stabilizer on the electrical properties of the second catalyst layer in one embodiment of the present invention.

[0043] Fig.28 This is a physical picture of the electrode for producing hydrogen by electrolyzing water in one embodiment of the present invention.

[0044] Fig.29 This is a physical picture of the electrode for producing hydrogen by electrolyzing water in a comparative example of the present invention.

[0045] Fig.30 For Fig.28 Actual picture of the electrode after ultrasonic treatment for 20 minutes.

[0046] Fig.31 For Fig.28 Actual picture of the electrode after ultrasonic treatment for 180 minutes.

[0047] Fig.32 For Fig.29 Actual picture of the electrode after ultrasonic treatment for 20 minutes.

[0048] Fig.33 For Fig.29 Actual picture of the electrode after ultrasonic treatment for 180 minutes.

[0049] Fig.34 for Fig.28 Scanning electron microscope image of the middle electrode.

[0050] Fig.35 for Fig.29 Scanning electron microscope image of the middle electrode.

[0051] Fig.36 This is a practical diagram comparing electrochemical solutions with and without stabilizers after being placed for 0 days in one embodiment of the present invention.

[0052] Fig.37 For the general Fig.36 Actual picture of the two electrochemical solutions after being left for 7 days.

[0053] Description of reference numerals:

[0054] Nanoparticles / first metal nanoparticles 101 , nanoparticle cluster structures / first metal nanoparticle cluster structures 110 , nanoparticles / second metal nanoparticles 102 , non-precious metal nanoparticles 103 , conductive carrier nanoparticles 104 , protective layer P, and dispersion layer D. DETAILED DESCRIPTION

[0055] The present invention is further described below through specific examples, but it should be pointed out that the specific material ratios, process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention and cannot be used to limit the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.

[0056] In the present invention, the preparation method of the catalyst may include:

[0057] S1. Preparation of nickel-sulfur alloy: ultrasonically dispersing a nickel salt and a dispersant in a water-ethanol mixed solvent formed by water and anhydrous ethanol in a volume ratio of 1-5:1-5 at a mass ratio of 100:10-20, wherein the nickel salt comprises at least one of nickel acetate, nickel sulfate, nickel nitrate and nickel chloride; and the dispersant comprises hexadecyltrimethylamine bromide, polyvinylpyrrolidone or a mixture of the two;

[0058] Then, a sulfiding agent solution is added dropwise to the system, wherein the sulfiding agent includes thioacetamide, and the mass ratio of the nickel salt to the sulfiding agent is 1-3:1-3; and the mixture is reacted at a temperature of 70-85°C for 10-15h, followed by washing, and then drying at a temperature of 60-70°C for 15-20h to obtain a nickel-sulfur alloy;

[0059] S2. The nickel-sulfur alloy, the nitrogen source and the carbon source prepared in step S1 are mixed to obtain a mixture, wherein the carbon source comprises dicyandiamide, the nitrogen source comprises urea, the molar ratio of the nitrogen source to the nickel-sulfur alloy is 1-3:0.1, and the molar ratio of the carbon source to the nickel-sulfur alloy is 1-3:0.1;

[0060] The mixture is sintered: the temperature is raised to 700-780°C at a rate of 3-5°C / min and kept at this temperature for 1-3h to obtain the catalyst.

[0061] In some embodiments, in step S1, a cobalt salt is further added to the system, the cobalt salt includes at least one of cobalt chloride, cobalt sulfate and cobalt nitrate, and the mass ratio of the nickel salt to the cobalt salt is 1-10:1.

[0062] In some embodiments, in step S2, carbon nanofibers with a particle size of 1-50 nm are further added to the mixture, and the mass ratio of the carbon nanofibers to the nickel-sulfur alloy is 0.01-0.03:0.1.

[0063] In some embodiments, the present application provides a catalyst prepared according to the preparation method described above.

[0064] In some embodiments, the present application provides an electrode sheet for producing oxygen by electrolysis of water, which comprises a substrate and an active material layer located on the substrate, wherein the active material layer comprises a catalyst prepared by the preparation method described above or the catalyst described above.

[0065] like Figure 1 As shown, in some embodiments of the present invention, the electrode catalyst may include a nanoparticle cluster structure 110, and the nanoparticle cluster structure 110 may be composed of nanoparticles 101. In an embodiment of the present invention, the nanoparticle cluster structure of the electrode catalyst may be less than or equal to 65nm, such as 10nm to 50nm, and 30nm to 50nm, and the nanoparticles may be less than or equal to 10nm, such as 1nm to 8nm, and 1nm to 6nm. Furthermore, the nanoparticle cluster structure 110 also includes a protective layer P, which is formed between the nanoparticles. The material of the protective layer P can be selected from at least one of citrate, carboxymethyl cellulose and polyacrylic acid, for example, to coat at least part of the nanoparticles 101, control the size of the nanoparticles, limit agglomeration, and improve the dispersibility of the nanoparticles. It is worth noting that in an embodiment of the present invention, an alloy electrocatalytic material with a smaller nanoparticle size and excellent dispersibility can be prepared by efficient and rapid reduction.

[0066] In some embodiments, the electrode catalyst may include nanoparticles of different metals. Specifically, the electrode catalyst may include first metal nanoparticles 101 (e.g. Figure 2 blue dots) and the second metal nanoparticles 102 (e.g. Figure 3 The size of the first metal nanoparticles and the second metal nanoparticles may be less than or equal to 10 nm, for example, 1 nm to 8 nm, and for example, 1 nm to 6 nm. The second metal nanoparticles 102 may be dispersed between the first metal nanoparticles 101 and / or the nanoparticle cluster structure 110, and at least partially cover at least a portion of the first metal nanoparticles 101. In some embodiments, the first metal nanoparticles may be aggregated to form the first metal nanoparticle cluster structure 110 (e.g. Figure 4), wherein the size of the first metal nanoparticle cluster structure is less than or equal to 65nm, for example, 10nm to 65nm, and for example, 30nm to 65nm. The size of at least 50% of the nanoparticle cluster structures may be less than or equal to 50nm, for example, 50% to 80% of the nanoparticle cluster structures may be less than or equal to 50nm.

[0067] In some embodiments, the nanoparticles of the electrode catalyst may further include non-precious metal nanoparticles 103, and the size of the non-precious metal nanoparticles may be less than or equal to 10 nm, for example, 1 nm to 8 nm, and for example, 1 nm to 6 nm. The material cost of the non-precious metal nanoparticles may be lower than the material cost of the first metal nanoparticles and / or the second metal nanoparticles. Therefore, the material cost of the electrode catalyst may be reduced by using non-precious metal nanoparticles. Specifically, Figure 5 As shown, the first metal nanoparticles 101 and / or the second metal nanoparticles 102 can be aggregated with the non-precious metal nanoparticles 103 to form a nanoparticle cluster structure to reduce the metal loading of the first metal nanoparticles 101 and / or the second metal nanoparticles 102, thereby reducing the material cost of the electrode catalyst. In the nanoparticle cluster structure, the metal loading of the first metal nanoparticles and / or the second metal nanoparticles can be less than or equal to 1 mg / cm 2 , for example 0.01 to 1 mg / cm 2 , for example 0.3~0.8mg / cm 2 .

[0068] For example, when applied to hydrogen production electrolysis electrodes, the first metal nanoparticles may be metal nanoparticles of platinum or platinum alloys, and the second metal nanoparticles may be metal nanoparticles of iridium or iridium alloys. By controlling the size and structural composition of the nanoparticles and nanoparticle cluster structures, the metal loading of the first metal nanoparticles 101 and / or the second metal nanoparticles 102 may be reduced, thereby reducing the material cost of the electrode catalyst. Among them, the material of the non-precious metal nanoparticles may be a transition metal, for example, at least one selected from titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au).

[0069] In some embodiments, Figure 6As shown, the electrode catalyst may also include conductive carrier nanoparticles 104, which may be formed between the nanoparticle cluster structure 110 and / or the nanoparticles 101 / 102 to reduce the metal loading of the first metal nanoparticles 101 and / or the second metal nanoparticles 102 in the catalyst. The material cost of the conductive carrier nanoparticles 104 may be lower than the material cost of the first metal nanoparticles 101 and / or the second metal nanoparticles 102, so the material cost of the electrode catalyst may be reduced by using the conductive carrier nanoparticles 104. The size of the conductive carrier nanoparticles 104 may be less than 100 nm, for example, less than or equal to 65 nm, and for example, equal to 30 nm to 65 nm. For example, the conductive carrier nanoparticles 104 may be conductive carrier nanoparticles of carbon, nickel or other metals.

[0070] In some embodiments, the electrode catalyst may further include a dispersion layer D, which may be formed between the nanoparticles to reduce the agglomeration of the nanoparticles and ensure the catalyst surface area of ​​the nanoparticles. Figure 4 In the embodiment, the dispersion layer D may be formed between the second metal nanoparticles 102 to reduce the aggregation of the second metal nanoparticles 102. The material of the dispersion layer may be selected from a mixture of one or more of (glycerol, citric acid (salt), carboxymethyl cellulose, sodium octadecyl sulfate, sodium dodecyl sulfate, polyvinyl pyrrolidone, cetylpyridinium chloride (bromide), stearic acid, oleic acid, lauric acid, polyacrylic acid, etc.). However, it is not limited thereto. In some embodiments, the second metal nanoparticles 102 may also aggregate to form a second metal nanoparticle cluster structure, wherein the size of the second metal nanoparticle cluster structure may be less than or equal to 50 nm, for example, 10 nm to 50 nm, and for example, 30 nm to 50 nm.

[0071] In some embodiments, the second metal nanoparticles 102 may at least partially cover at least a portion of the surface of the nanoparticle cluster structure 110 , for example Figure 2 to Figure 4 , Figure 7 As shown, the nanoparticle cluster structure (i.e., the first nanoparticle cluster structure 110) may be composed of first metal nanoparticles and / or non-precious metal nanoparticles. When the material cost of the second metal nanoparticles is higher than the material cost of the first metal nanoparticles and the non-precious metal nanoparticles, the metal loading of the second metal nanoparticles in the catalyst may be reduced by coating at least part of the surface of the nanoparticle cluster structure, thereby reducing the material cost of the electrode catalyst. In the electrode catalyst, the metal loading of the second metal nanoparticles may be less than or equal to 1 mg / cm 2 , for example 0.01 to 1 mg / cm 2 , for example 0.5~1mg / cm 2 .

[0072] The embodiments of the present invention can control the size of nanoparticles, limit agglomeration, improve the dispersibility of nanoparticles, and can efficiently and quickly reduce and prepare electrocatalytic materials with smaller nanoparticle size and excellent dispersibility under a mild reaction environment. Figure 1 Shown is the SEM image of the nanoparticles prepared in the embodiment of the present invention, Figure 8 The SEM image of the conventional nanoparticles is shown. Figure 1 The average particle size of nanoparticles is about 5nm. Figure 8 The average particle size of the nanoparticles is about 50 nm, which shows that the method of the embodiment of the present invention can control the size of the nanoparticles and limit agglomeration. Fig. 9 The photo shows the nanoparticles of the present invention (left) and the traditional nanoparticles (right) after standing in the ethanol dispersion for 48 hours. Fig. 9 It can be seen that the embodiments of the present invention can limit agglomeration and improve the dispersibility of nanoparticles. In general, the catalyst of the present invention not only has a simple preparation process, but also has good catalytic efficiency and is suitable for large-scale production.

[0073] For example, a cathode electrode (electrode sheet or membrane electrode) in an electrolytic cell may include a nanoparticle cluster structure 110 composed of first metal nanoparticles 101 and non-precious metal nanoparticles 103. For another example, an anode electrode (electrode sheet or membrane electrode) in an electrolytic cell may include second metal nanoparticles 102, and the second metal nanoparticles 102 may at least partially cover the nanoparticle cluster structure 110.

[0074] In one embodiment, the present invention further provides a high entropy nanoparticle cluster, the high entropy nanoparticle cluster comprises at least three metal elements, and the nanoparticle agglomeration size of the high entropy nanoparticle cluster can be less than 50nm, such as Fig.10 As shown, for example, it can be less than or equal to 30nm, so that the size of its nanocluster can be controlled, so that the active sites are highly exposed, the mass transfer channels are sufficient, and the conductivity is high. Fig.11 In the comparative example shown, the agglomeration size of the conventional nanoparticles is greater than 100 nm, while the active sites of the high entropy nanoparticle clusters of the present invention are more exposed and have higher conductivity.

[0075] In one embodiment of the present invention, the surface of the nano-catalyst structure may have a plurality of holes, and the size of the holes is less than 80 nm.

[0076] In one embodiment of the present invention, the nanocatalyst structure includes a coral-like dealloyed nanowire array structure, and the nanowire array structure has a coral-like porous structure. The length of the nanowire array is, for example, 10 μm to 1100 μm, and the diameter of the nanowire is, for example, 120 nm to 200 nm. In this embodiment, the electrode catalyst includes at least metal element A and element B, wherein element A is selected from at least one of transition metals such as Mn, Cr, Fe, Co, Ni or Cu, and element B is selected from precious metals such as Ir. By forming a coral-like porous structure, the specific surface area of ​​the electrode catalyst is increased, thereby increasing the contact area with water under the same mass and improving the catalytic efficiency.

[0077] In one embodiment of the present invention, the specific surface area of ​​the electrode catalyst is, for example, 10 m 2 / g. This increases the electrochemical specific surface area of ​​the electrode catalyst, exposes high active sites, provides a large number of mass transfer channels, and improves the catalytic performance of the electrode catalyst. After the electrode catalyst is used to make a membrane electrode, the amount of precious metals in the catalyst layer is greatly reduced, which greatly reduces the cost.

[0078] In another embodiment of the present invention, the nanocatalyst structure includes a hollow spherical structure or a hollow chain structure, wherein in the hollow spherical structure, the diameter of the hollow spherical structure is, for example, 3nm to 25nm. In the hollow chain structure, the length of the hollow chain is, for example, 10μm to 1100μm, and the diameter of the hollow sphere on the hollow chain is, for example, 0.5μm to 1.5μm. The electrode catalyst of the hollow structure has a regular shape and uniform size, which is conducive to the transmission of the fluid.

[0079] In another embodiment of the present invention, the electrode catalyst includes at least two of a transition metal, a lanthanide rare earth element, and a platinum group noble metal element, wherein the transition metal includes, for example, at least one of Mn, Cr, Zr, Fe, Co, Ni, Cu, Zn, Mo, or W, and the platinum group noble metal element includes at least one of Ru, Rh, Pd, Ag, Os, Ir, Pt, or Au. In one embodiment of the present invention, the electrocatalyst includes, for example, the following components in mass percentage: 70% of a transition metal, 30% of a lanthanide rare earth element and / or a platinum group noble metal element, and the remainder is oxygen. In one embodiment of the present invention, the specific surface area of ​​the electrode catalyst is, for example, 15 to 25 m 2 / g. By forming a hollow spherical electrode catalyst, the electrochemical specific surface area of ​​the electrode catalyst can be increased. At the same time, the hollow structure improves the mass transfer efficiency and strength of the catalyst, thereby improving the catalytic performance of the electrode catalyst.

[0080] In one embodiment of the present invention, in order to obtain electrode catalysts of different morphologies, different metal precursor solutions can be selected. In a specific embodiment of the present invention, in order to obtain an electrode catalyst with a coral-like porous structure, the metal precursor solution includes at least one of transition metals such as Mn, Cr, Fe, Co, Ni or Cu, and precious metals such as Ir. In another specific embodiment of the present invention, in order to obtain an electrode catalyst with a hollow spherical structure or a hollow chain structure, the metal precursor solution includes at least two of transition metals, lanthanide rare earth elements and platinum group precious metal elements, wherein the transition metal includes, for example, at least one of Mn, Cr, Zr, Fe, Co, Ni, Cu, Zn, Mo or W, and the platinum group precious metal elements include at least one of Ru, Rh, Pd, Ag, Os, Ir, Pt or Au.

[0081] In one embodiment of the present invention, different morphology induction layers can be used to obtain nanocatalyst structures with different morphologies. In one embodiment of the present invention, in order to obtain an electrode catalyst with a coral-like porous structure, a first inducer and a second inducer can be added in sequence, the first inducer includes solvents such as metal acid salts, metal halides, metal sulfates, and metal nitrates, the metal is selected from at least two of Mn, Cr, Fe, Co, Ni, Cu, Zn, and platinum group noble metal elements, and the second inducer is selected from at least one of organic solvents such as methanol, ethanol, propanol, acetone, dimethylformamide, cyclohexane, ethyl acetate, and dimethyl sulfoxide. The (molar) ratio of the metal precursor solution, the first inducer, and the second inducer is, for example, 1:1 to 1:10.

[0082] In another embodiment of the present invention, in order to obtain an electrode catalyst with a hollow spherical structure or a hollow chain structure, the organic inducer in the catalyst is selected from, for example, isophthalic acid esters, phthalates, 1,4-diazabicyclo[2.2.2]octane, triethylenediamine, 1,4-dimethylpiperazine, hexamethylenetetramine, pyromellitic acid, trimesic acid, 1,4-di(1H-pyrazol-4-yl)benzene, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracarboxylic acid, 2,4,6-tri(4-pyridyl)-1,3 ,5-triazine, tris(isobutylaminoethyl)amine, bis(3,5-dicarboxyphenyl)azo, biphenyl dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-phenylene diacetic acid, 1,1,2,2-tetra(4-carboxyphenyl)ethylene, 1,3,5-tris(4-carboxyphenyl)benzene, 2-(diphenylphosphino)terephthalic acid, 2-amino-4-hydroxy-6-methylpyrimidine, 2-methylimidazole, 2-aminoterephthalic acid, terephthalic acid, fumaric acid and trioctyl trimellitate. The molar concentration ratio of the organic inducer to the total metal ion in the metal precursor solution is, for example, 1:10000 to 100:1.

[0083] In one embodiment of the present invention, different metal precursor solutions and morphology inducing layers are selected according to the morphology or performance requirements of the electrode catalyst to be obtained, so as to achieve the production requirements of different morphologies.

[0084] In one embodiment of the present invention, the intermediate is obtained by stirring at a preset temperature for a preset time. In one embodiment of the present invention, for example, the pH value of the mixed solution of the metal precursor solution and the morphology inducing agent is controlled to obtain solid intermediates with different morphologies.

[0085] In one embodiment of the present invention, the electrode catalyst can obtain different morphologies under the conditions of the first inducer and the second inducer to obtain a coral-like dealloyed nanowire array structure. In another specific embodiment of the present invention, under the conditions of an organic inducer, a spherical or spherical chain structure can be obtained.

[0086] In one embodiment of the present invention, when forming pores in the intermediate, for example, pickling treatment or calcination treatment can be used to remove part of the metal, form holes on the catalyst surface, and obtain a porous electrode catalyst. The specific selection is based on the preset morphology of the electrode catalyst to be manufactured.

[0087] In one embodiment of the present invention, when the coral-like dealloyed nanowire array structure is pore-formed, the pore-formation is performed by, for example, acid washing.

[0088] In another embodiment of the present invention, when holes are formed in a spherical or ball-chain structure, for example, by acid washing or calcining, a hollow structure can be obtained.

[0089] In the present invention, by selecting different metal precursor solutions and morphology inducing layers, the production requirements of different morphologies are achieved, and then according to the produced morphologies, different pore-making methods are selected to obtain a nanocatalyst structure, and the surface of the nanocatalyst structure has multiple holes. By controlling the pore-making time, the size of the hole is controlled to be less than 80nm to meet the catalytic requirements.

[0090] like Fig.12 As shown in FIG. 1 , the electrode catalyst of an embodiment of the present application is observed by a scanning electron microscope (SEM), and a scanning electron microscope image is obtained. Fig.12 It can be seen that the microscopic morphology of the electrode catalyst prepared in this embodiment is: a coral-like nanowire array structure constitutes a nanocatalyst structure, the length of the nanowire array is, for example, 10μm to 1100μm, and the diameter of the nanowire is, for example, 120nm to 200nm. After testing, the electrode catalyst prepared in this embodiment includes 70% M, 20% N, and 10% oxygen, and the elements are evenly distributed, which improves the consistency of the catalytic effect.

[0091] like Fig.13 and Fig.14 As shown, the electrode catalyst of another embodiment of the present application was observed by scanning electron microscope, and the Fig.13 and Fig.14 The scanning electron microscope image shown. Figure 2 It can be seen that the microscopic morphology of the electrode catalyst prepared in this embodiment is: a hollow spherical structure, and the diameter of the hollow spherical structure is, for example, 3nm to 25nm. Figure 3 It can be seen that the microscopic morphology of the electrode catalyst prepared in this embodiment is: a hollow chain structure, and the length of the hollow chain is, for example, 10 μm to 1100 μm, and the diameter of the hollow sphere on the hollow chain is, for example, 0.5 μm to 1.5 μm.

[0092] like Fig.15 As shown, Fig.12 The actual picture and performance curve of the membrane electrode prepared by the electrode catalyst shown in the figure. Fig.15 It can be seen that the electrode catalyst can be evenly distributed on the substrate to form a membrane electrode, and the product quality of the membrane electrode is high. From the function of voltage versus current density, it can be seen that the electrolysis voltage is 2.02V at 2A·cm-2, and the electrode electrolysis voltage is low, indicating that the amount of Ir used can be reduced and the production cost can be reduced.

[0093] In one embodiment of the present invention, a special-shaped water electrolysis catalyst provided by the present invention is used in a water electrolysis hydrogen production device. Fig.16 As shown, the shaped electrolytic water catalyst includes a shaped nanocatalyst structure 10 and a morphology inducing layer 20. The morphology inducing layer 20 can be formed on a portion of the surface of the shaped nanocatalyst structure. In one embodiment of the present invention, the morphology inducing layer 20 is, for example, at least one layer. When the morphology inducing layer 20 is multi-layered, the multi-layer morphology inducing layer is sequentially stacked on the shaped nanocatalyst structure. In one embodiment of the present invention, the specific surface area of ​​the shaped electrolytic water catalyst is, for example, greater than or equal to 100 m 2 / g, for example, 100 to 1000 m 2 / g. By forming heterogeneous nanocatalysts, the specific surface area of ​​the catalyst is larger, which increases the catalytic performance. At the same time, when forming a membrane electrode, the porosity can be increased, the bed pressure drop can be reduced, which is beneficial to the diffusion of water and the catalytic efficiency can be accelerated. In addition, the heterogeneous catalyst can improve the processing performance in the process of forming a membrane electrode.

[0094] See also Figures 16 to 21As shown, in one embodiment of the present invention, the shape of the special-shaped electrolytic water catalyst is, for example, one or more combinations of a polyhedron, a needle, a pointed prism, a sphere, a chain or a fused sphere, etc., which can be specifically controlled according to the manufacturing process. Among them, when the shape of the special-shaped electrolytic water catalyst is different, the size of the special-shaped electrolytic water catalyst is different, which is specifically determined according to the morphology of the formed heterogeneous nanocatalyst. By forming special-shaped electrolytic water catalysts of different shapes and sizes, when applied to electrode sheets or membrane electrodes of electrochemical devices (such as electrolyzers or batteries), electrode sheets or membrane electrodes with different catalytic abilities can be formed to meet the use under different environments or requirements.

[0095] In another embodiment of the present invention, the special-shaped water electrolysis catalyst includes at least two of a transition metal, a lanthanide rare earth element and a platinum group noble metal element, wherein the transition metal includes, for example, at least one of Mn, Cr, Zr, Fe, Co, Ni, Cu, Zn, Mo or W, and the platinum group noble metal element includes at least one of Ru, Rh, Pd, Ag, Os, Ir, Pt or Au.

[0096] In one embodiment of the present invention, the material of the shaped nano-catalyst structure is at least one of metal, alloy or metal oxide, etc., and the material of the morphology inducing layer is at least one of metal, alloy or metal oxide, etc. The material of the shaped nano-catalyst structure and the material of the morphology inducing layer may be the same or different, depending on the target catalytic use (function), such as using metals and alloys in the cathode for hydrogen production and metal oxides in the anode for oxygen production.

[0097] In one embodiment of the present invention, in the metal precursor solution, the metal elements include at least two of transition metal elements, lanthanide rare earth elements and platinum group noble metal elements, wherein the transition metal elements include, for example, at least one of Mn, Cr, Zr, Fe, Co, Ni, Cu, Zn, Mo or W, and the platinum group noble metal elements include at least one of Ru, Rh, Pd, Ag, Os, Ir, Pt and Au, and the solvent of the metal precursor solution includes pure water, ultrapure water, deionized water or tap water. The metal elements come from metal salts soluble in water such as metal acid salts, metal halides, metal sulfates or metal nitrates, and the metal salts are added to the solvent, for example, by ultrasonic stirring for 2min to 5min to obtain a metal precursor solution. In other embodiments, dissolution can also be performed by other methods. In the metal precursor solution, the concentration of total metal ions is, for example, 0.01 to 1M.

[0098] In one embodiment of the present invention, in order to obtain a shaped electrolytic water catalyst of different shapes, a morphology inducing layer is used, and the material of the morphology inducing layer is selected from, for example, isophthalic acid esters, phthalates, 1,4-diazabicyclo[2.2.2]octane, triethylenediamine, 1,4-dimethylpiperazine, hexamethylenetetramine, pyromellitic acid, trimesic acid, 1,4-di(1H-pyrazol-4-yl)benzene, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracarboxylic acid, 2,4,6-tri(4-pyridyl)-1,3, At least one of 5-triazine, tris(isobutylaminoethyl)amine, bis(3,5-dicarboxyphenyl)azo, biphenyl dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-phenylene diacetic acid, 1,1,2,2-tetra(4-carboxyphenyl)ethylene, 1,3,5-tris(4-carboxyphenyl)benzene, 2-(diphenylphosphino)terephthalic acid, 2-amino-4-hydroxy-6-methylpyrimidine, 2-methylimidazole, 2-aminoterephthalic acid, terephthalic acid, fumaric acid, trioctyl trimellitate, etc. The molar concentration ratio of the organic induction layer to the total metal ion in the metal precursor solution is, for example, 1:10000 to 100:1.

[0099] In one embodiment of the present invention, different metal precursor solutions and morphology induction layers are selected according to the morphology or performance requirements of the preset special-shaped electrolytic water catalyst to be obtained, so as to achieve the production requirements of different morphologies. That is, by being able to control the reaction raw materials and reaction conditions, a special-shaped electrolytic water catalyst with preset morphology requirements can be obtained.

[0100] In one embodiment of the present invention, in order to obtain a shaped electrolytic water catalyst having a multi-layer morphology inducing layer, a morphology inducing layer can be in-situ grown on the shaped electrolytic water catalyst to obtain a shaped electrolytic water catalyst having a multi-layer morphology inducing layer. The material of the multi-layer morphology inducing layer can be exactly the same as the material of the shaped nanocatalyst structure, or it can be partially different or completely different.

[0101] like Figures 16 to 19 As shown in FIG. 1 , scanning electron microscope images of the shaped water electrolysis catalysts in different embodiments of the present application were observed by scanning electron microscope (SEM). Fig.16 It can be seen that the microscopic morphology of the special-shaped electrolytic water catalyst is: a hexagonal special-shaped electrolytic water catalyst, and the side length of the hexagon is, for example, 0.1 μm to 1.5 μm. Fig.17 It can be seen that the microscopic morphology of the special-shaped electrolytic water catalyst is: a needle-shaped special-shaped electrolytic water catalyst, and the length of the nanocatalyst structure is, for example, 0.2 μm to 5 μm. Fig.18 It can be seen that the microscopic morphology of the special-shaped electrolytic water catalyst is: a special-shaped electrolytic water catalyst with a pointed prism shape, and the length of the nanocatalyst structure is, for example, 0.01 μm to 2 μm. Fig.19It can be seen that the microscopic morphology of the irregular electrolytic water catalyst is: an irregular electrolytic water catalyst fused with a spherical shape, and the diameter of the sphere is, for example, 0.01 μm to 0.5 μm. That is, by selecting different metal precursors and morphology inducing layers, irregular electrolytic water catalysts with different morphologies can be obtained.

[0102] like Fig. 20 As shown, the shaped water electrolysis catalyst was observed by scanning electron microscopy. Fig. 20 The scanning electron microscope image and the energy-dispersive X-ray spectroscopy (EDS) image are shown. The microscopic morphology of the shaped electrolytic water catalyst is: a shaped electrolytic water catalyst with a chain structure, and the length of the chain is, for example, 8μm to 1000μm, and only part of the length is shown in the figure. After testing, the shaped nanocatalyst structure prepared in this embodiment includes 50% transition metal, 45% noble metal, 5% oxygen, and the material of the morphology induction layer is the same as that of the shaped nanocatalyst structure.

[0103] like Fig.21 As shown, the shaped water electrolysis catalyst of Example 1 was observed by scanning electron microscope, and a scanning electron microscope image and an X-ray energy spectrum diagram were obtained. After detection, the shaped nanocatalyst structure prepared in this example includes 50% transition metal, 45% noble metal, 5% oxygen, and the material of the morphology inducing layer is the same as that of the shaped nanocatalyst structure.

[0104] In some embodiments, the electrode catalyst layer may include nanoparticles, nanowires, nanochains or other nanostructures. In some embodiments, the precious metal (e.g., platinum) or alloy inside and on the surface of the nanostructure of the electrode catalyst may be in different proportions, or in a gradient change, so as to correspondingly improve the catalyst performance of the electrode. For example, the nanostructure of the electrode catalyst may include a first metal catalyst layer and a second metal catalyst layer, the second metal catalyst layer being formed on the first metal catalyst layer, wherein the alloy ratio of the first metal catalyst is different from the alloy ratio of the second metal catalyst layer. For example, the precious metal ratio of the second metal catalyst layer in the outer layer may be higher than the precious metal ratio of the first metal catalyst layer in the inner layer. In one embodiment, the number of precious metal nanoparticles in the second metal catalyst layer in the outer layer may be higher than the number of precious metal nanoparticles in the first metal catalyst layer in the inner layer. Since the precious metal (e.g., platinum) catalyst may have better activity, the external catalytic efficiency of the nanostructure of the electrode catalyst may be improved by different alloy ratios inside and outside the nanostructure of the electrode catalyst or different numbers of metal nanoparticles (101, 102, 103).

[0105] In one embodiment, the nanostructure of the electrode catalyst may include a first metal catalyst layer, a second metal catalyst layer, a third metal catalyst layer or more metal catalyst layers, and the alloy ratios of these metal catalyst layers are all different.

[0106] In one embodiment, the nanostructure of the electrode catalyst may be, for example, a nanowire or a nanochain, and the nanowire or nanochain may include a first metal nanoparticle 101 and a second metal nanoparticle 102, wherein the number of the second metal nanoparticles 102 on the surface of the nanostructure (such as a nanowire or a nanochain) of the electrode catalyst may be greater than the number of the second metal nanoparticles 102 inside the nanostructure (such as a nanowire or a nanochain) of the electrode catalyst, and at this time, the activity of the second metal nanoparticles 102 (such as platinum, iridium or other precious metals) may be higher than that of the first metal nanoparticles 101 (such as nickel). Therefore, the catalytic performance of the overall electrode catalyst may be improved by having more second metal nanoparticles 102 on the surface of the nanostructure (such as a nanowire or a nanochain) of the electrode catalyst. Among them, the particle ratio of the first metal nanoparticle 101 in the nanostructure (such as a nanowire or a nanochain) may be 75% to 99%, and the particle ratio of the second metal nanoparticle 102 in the nanostructure (such as a nanowire or a nanochain) may be 1% to 25%. In one embodiment, the number of particles of the second metal nanoparticle 102 in the nanostructure may also increase from the inside to the outside in a proportional manner, for example.

[0107] In some embodiments, when the electrode catalyst is formed on the oxygen evolution side anode (membrane electrode or electrode sheet) of the water electrolysis device, the iron / nickel (Fe / Ni) molar ratio on the surface of the electrode catalyst can be between 0.1 and 0.5 to obtain better oxygen evolution reaction performance. In some embodiments, the iron / nickel molar ratio on the surface of the anode catalyst can be, for example, between 0.15 and 0.45, and for example, between 0.15 and 0.3.

[0108] In some embodiments, nano-metal oxide particles can be combined with multiple holes in the electrode catalyst nanostructure to fully expose the active sites, thereby enhancing the activity of the catalyst. For example, precious metal (such as iridium oxide IrO2) nanoparticles can be combined with the porous structure of the catalyst structure to reduce the amount of precious metal (such as iridium or platinum) and fully expose the active sites. Among them, the catalyst can be synthesized by in-situ growth or electrochemical methods, and the porous substrate of the catalyst can be, for example, carbon, platinum, nickel, chromium or other substrates. Specifically, the intermediate and the nano-metal oxide particles can be synthesized by in-situ growth or electrochemical methods to obtain the electrode catalyst. However, in some embodiments, the nano-metal oxide particles can also include nickel, iron, platinum, ruthenium and / or other metal elements. In some embodiments, the porous substrate of the catalyst can be, for example, porous nanowires. When preparing the electrode catalyst described above, the preparation method can, for example, include: preparing a metal precursor solution; keeping warm and stirring at a preset temperature for a preset time to obtain an intermediate, wherein the intermediate surface has multiple holes; and synthesizing the intermediate and the nano-metal oxide particles to obtain the electrode catalyst.

[0109] In some embodiments, the nanostructure of the electrode catalyst may be, for example, a plurality of nanocluster structures, and the nanocluster structure may be composed of a plurality of nanosheets, and the size of the nanosheets may be, for example, less than 2 nm. The size of the nanocluster structure may be, for example, less than 150 nm, and the nanocluster structure composed of a plurality of nanosheets may be, for example, spherical, columnar, or other shaped structures. Through such a nanocluster structure, the catalytic surface area of ​​the electrode catalyst may be increased to improve the catalytic efficiency.

[0110] In some embodiments, when the electrode catalyst is applied to an electrode of a seawater hydrogen production electrolyzer, the surface of the electrode catalyst may include a metal or an oxidized metal that can suppress hydrogen ions, such as a platinum-based material, to protect the electrode from chloride ion corrosion and extend its service life.

[0111] In some embodiments, when the electrode catalyst is applied to an electrode of a hydrogen production electrolyzer, the electrolyte in the electrolyzer may include oxygen anions, such as phosphate, borate, sulfate, and carbonate, to inhibit the dissolution of the electrode catalyst, thereby improving the stability and electrolysis performance of the catalyst.

[0112] The present invention also provides a water electrolysis device, comprising the electrode catalyst as described above, and the electrode catalyst is loaded on a proton exchange membrane, an anion exchange membrane, or a diffusion layer to form a membrane electrode or an electrode sheet. The electrode catalyst has a high electrochemical surface area, high exposure of active sites, and a large number of mass transfer channels, which can improve catalytic efficiency and reduce production costs.

[0113] In some embodiments, the electrode catalyst can be applied to a hydrogen production electrolysis unit or a hydrogen production electrolyzer, such as a proton exchange membrane (PEM) electrolyzer, an anion exchange membrane (AEM) electrolyzer, an alkali solution electrolyzer, a solid oxide (SOEC), a seawater hydrogen production electrolyzer, or other electrolyzer electrodes using catalyst electrodes. Specifically, the electrode catalyst of the present application can be formed on different substrates to form an electrode sheet or a membrane electrode. However, it is not limited to this. In other embodiments, the electrode catalyst can also be applied to electrodes of other electrochemical devices, such as electrodes of fuel cells or other electrochemical electrolyzers.

[0114] In some embodiments, when preparing an electrode (membrane electrode or electrode sheet) for a hydrogen production electrolyzer, the preparation method may include at least steps S11-S13.

[0115] S11. Provide a substrate.

[0116] S12, forming a first catalyst layer on the substrate.

[0117] S13. Forming a second catalyst layer on the first catalyst layer, wherein when forming the second catalyst layer, the electrochemical solution includes an electrochemical solution stabilizer, and the electrochemical solution stabilizer includes one or more combinations of sodium citrate, potassium citrate, sodium gluconate, disodium ethylenediaminetetraacetate and sodium tartrate.

[0118] See also Fig. 22 As shown, in one embodiment of the present invention, in step S11, the substrate is, for example, a nickel mesh, nickel foam, nickel felt, carbon cloth, a diffusion layer substrate or a porous substrate. Furthermore, the substrate should be pretreated before use to remove impurities on the surface of the substrate so that the substrate can be tightly combined with the first catalyst layer formed subsequently. In one embodiment of the present invention, the pretreatment includes, for example, placing the substrate in a solvent at a preset temperature and soaking it for a preset time, then taking out the substrate and rinsing it with deionized water, and then placing it in an oven to dry. Among them, the solvent includes, for example, at least one of methanol and ethanol, the preset temperature is, for example, 50°C-90°C, and the preset time is, for example, 0.5h-5h.

[0119] See also Fig. 22As shown, in one embodiment of the present invention, after the substrate is pretreated, the substrate is also etched. Among them, the etching method is, for example, dry etching or wet etching. In this embodiment, the etching method is, for example, electrochemical etching. Specifically, the substrate is immersed in an etching solution, the substrate is connected to the positive electrode of the power supply, the reference electrode is connected to the negative electrode of the power supply, and then a voltage is applied to the substrate to dissolve the surface of the substrate to etch the surface of the substrate. Among them, the reference electrode is, for example, a platinum electrode or a carbon electrode, the voltage is, for example, 3V-5V, the time of electrochemical etching is, for example, 30s-60s, the roughness of the substrate surface before etching is, for example, 0.05μm-0.1μm, and the roughness of the substrate surface after etching is, for example, 0.4μm-0.8μm. By etching, the roughness of the substrate surface can be increased, so that the substrate and the subsequently formed electrode catalyst layer (such as the first catalyst layer and the second catalyst layer) can be closely combined, and the stability of the electrode catalyst layer on the substrate is improved.

[0120] See also Fig. 22 As shown, in one embodiment of the present invention, after etching the substrate, in step S12, a first catalyst layer is formed on the substrate. The present invention does not limit the material and formation method of the first catalyst layer, which can be selected according to actual needs. In this embodiment, the first catalyst layer is, for example, a multi-element alloy layer composed of nickel-precious metals, and the material of the first catalyst layer includes, for example, soluble nickel salts, soluble precious metal salts, soluble alkalis and solvents, etc., soluble nickel salts include, for example, one or more combinations of nickel acetate, nickel chloride, nickel nitrate, nickel citrate, nickel sulfate and nickel sulfamate, etc., soluble precious metal salts include, for example, soluble platinum salts, etc., soluble platinum salts include, for example, one or more combinations of platinum nitrate, platinum sulfate and platinum chloride, etc., soluble alkalis include, for example, one or more combinations of sodium hydroxide, potassium hydroxide and ammonium bicarbonate, etc., and solvents include, for example, one or more combinations of pure water, ultrapure water, deionized water, ethanol, ethylene glycol, propanol and isopropanol, etc.

[0121] See also Fig. 22As shown, in one embodiment of the present invention, in step S12, the method for forming the first catalyst layer is, for example, spraying, electrodeposition or in-situ growth. In the present embodiment, the method for forming the first catalyst layer is, for example, in-situ growth. Specifically, a preset ratio of soluble nickel salt, soluble precious metal salt and soluble alkali is weighed and added to a solvent and mixed evenly to obtain a mixed solution, and then the substrate is immersed in the mixed solution, and the mixed solution and the substrate are heated to a preset temperature at the same time, and the preset time is kept warm, and the soluble nickel salt and the soluble precious metal salt are grown in-situ on the substrate to obtain the first catalyst layer. Among them, the molar concentration ratio of the soluble nickel salt, the soluble precious metal salt and the soluble alkali solvent is, for example, (1-4): (0.002-0.04): (1-2), the preset temperature is, for example, 30°C-90°C, and the insulation time is, for example, 240min-420min.

[0122] See also Fig. 22 As shown, in one embodiment of the present invention, after forming the first catalyst layer, in step S13, a second catalyst layer is formed on the first catalyst layer. For example, the second catalyst layer can be formed by an electrochemical method. Specifically, the substrate is immersed in an electrochemical solution, and the metal components in the electrochemical solution are deposited on the first catalyst layer to form the second catalyst layer. Wherein, the second catalyst layer is, for example, a nickel-iron alloy layer, the electrochemical solution includes, for example, soluble metal salts, reagents, and electrochemical solution stabilizers, etc., the soluble metal salts include, for example, one or more combinations of soluble nickel salts and soluble iron salts, etc., the soluble nickel salts include, for example, one or more combinations of nickel sulfate, nickel chloride, nickel sulfamate, and nickel nitrate, etc., the soluble iron salts include, for example, one or more combinations of ferrous sulfate and ferrous chloride, etc., the reagents include, for example, one or more combinations of pure water, ultrapure water, and deionized water, etc., the electrochemical solution stabilizer includes, for example, one or more combinations of sodium citrate, potassium citrate, sodium gluconate, disodium ethylenediaminetetraacetic acid, and sodium tartrate, etc., and the reference electrode is, for example, a nickel electrode, a platinum electrode, or a carbon electrode, etc. By adding an electrochemical solution stabilizer, the stability of the second catalyst layer on the substrate is improved, so that the second catalyst layer is not easily separated from the substrate, thereby allowing the catalytic activity of the second catalyst layer to function normally.

[0123] See also Fig. 22 As shown, in one embodiment of the present invention, in step S13, when preparing the electrochemical solution, the concentration of the electrochemical solution stabilizer in the electrochemical solution is, for example, 0.5 g / L-1 g / L. Fig. 22 , Figure 36 to Figure 37As shown, in one embodiment of the present invention, through visual observation, when the concentration of the electrochemical solution stabilizer added to the electrochemical solution is greater than 0.5g / L, the color of the electrochemical solution does not change after being placed for 7 days, while the electrochemical solution without the electrochemical solution stabilizer begins to become turbid after more than 3 hours, the electrochemical solution becomes invalid, and the color of the electrochemical solution changes significantly after being placed for 7 days.

[0124] See also Figure 22 to Figure 26 As shown, in one embodiment of the present invention, for example, the influence of different concentrations of electrochemical solution stabilizers on the plating property of the electrochemical solution is analyzed by using a Hastelloy sheet. Specifically, when the concentration of the electrochemical solution stabilizer is greater than 1g / L, the plating property of the electrochemical solution on the Hastelloy sheet is affected. When the concentration of the electrochemical solution stabilizer is less than 1g / L, within the available current density range, the plating property of the electrochemical solution on the Hastelloy sheet is basically not affected. The available current density range is, for example, less than 2ASD.

[0125] See also Fig. 22 and Fig. 27 As shown, in one embodiment of the present invention, for example, the influence of different concentrations of electrochemical solution stabilizer on the electrical properties of the second catalyst layer is analyzed. Specifically, when the concentration of the electrochemical solution stabilizer is less than 1g / L, the electrical properties of the second catalyst layer are basically not affected. When the concentration of the electrochemical solution stabilizer is greater than 1.5g / L, the electrical properties of the second catalyst layer have a significant decrease. Therefore, by Figure 23 to Figure 27 The analysis and testing show that maintaining the concentration of the electrochemical solution stabilizer in the electrochemical solution at, for example, 0.5 g / L-1 g / L can increase the timeliness of the electrochemical solution and prevent the electrochemical solution stabilizer from affecting the platability of the electrochemical solution and the electrical properties of the second catalyst layer.

[0126] See also Fig. 22 and Fig.28 As shown, in one embodiment of the present invention, after completing steps S11-S13, an electrolytic water hydrogen production electrode is obtained. The physical diagram of the electrolytic water hydrogen production electrode is as shown in FIG. Fig.28 In addition, the present invention also provides a comparative example of preparing an electrode for producing hydrogen by electrolysis of water, and the actual picture of the comparative example is as shown in FIG. Fig.29 As shown, the preparation method of the comparative example is Fig.28 The difference between the preparation methods of the embodiments is that the substrate is not etched in the comparative example, and the remaining steps are exactly the same.

[0127] See also Fig. 22 , Figures 28 to 33As shown, in one embodiment of the present invention, for the water electrolysis hydrogen production electrode in the embodiment and the comparative example, the electrode is cleaned by, for example, an ultrasonic cleaning machine to test the bonding force between the second catalyst layer and the substrate. The ultrasonic power is, for example, 30W-40W, and the ultrasonic treatment time is, for example, 100min-300min. Fig.30 and Fig.32 It can be seen that after 20 minutes of ultrasonic treatment, the second catalyst layer and the first catalyst layer on the water electrolysis hydrogen production electrode in the comparative example are completely separated from the substrate, while the second catalyst layer and the first catalyst layer on the water electrolysis hydrogen production electrode in the embodiment do not fall off from the substrate. Fig.31 and Fig.33 It can be seen that after 180 minutes of ultrasonic treatment, the second catalyst layer and the first catalyst layer on the water electrolysis hydrogen production electrode in the embodiment are still covered on the surface of the substrate without any shedding phenomenon. Therefore, by etching the substrate and increasing the roughness of the substrate surface, the bonding between the substrate and the catalyst layer can be improved, and the stability of the catalyst layer on the substrate can be improved.

[0128] See also Fig. 22 , Fig.28 , Fig.29 , Figure 34 to Figure 35 As shown, in one embodiment of the present invention, for example, the water electrolysis hydrogen production electrodes of the embodiment and the comparative example are observed by scanning electron microscope. Fig.34 and Fig.35 It can be seen that the morphology of the second catalyst layer in the embodiment is similar to that of the second catalyst layer in the comparative example, indicating that etching the substrate will not affect the growth of the second catalyst layer. Moreover, relative to the second catalyst layer in the comparative example, the second catalyst layer in the embodiment has better stability on the substrate. Therefore, by etching the substrate, the uniformity of the distribution of the second catalyst layer on the substrate can be improved, thereby improving the performance of the water electrolysis hydrogen production electrode.

[0129] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. An electrode for a seawater hydrogen production electrolyzer, characterized in that: include: Base material; The catalyst layer has a surface comprising a metal or metal oxide of a platinum-based material.

2. The electrode of the seawater hydrogen production electrolyzer according to claim 1, characterized in that: The catalyst layer may include nanoparticles, nanowires, nanochains or nanosheet structures.

3. The electrode of the seawater hydrogen production electrolyzer according to claim 1, characterized in that: The catalyst layer includes a first metal catalyst layer and a second metal catalyst layer, and the first metal catalyst layer and the second metal catalyst layer have different alloy ratios.

4. A method for preparing an electrode for a seawater hydrogen production electrolyzer, characterized in that: At least the following steps are included: providing a substrate; A catalyst layer is formed on the substrate, wherein a surface of the catalyst layer includes a metal or an oxidized metal of a platinum-based material.

5. The preparation method according to claim 4, characterized in that: The step of forming the catalyst layer comprises: preparing a metal precursor solution; Keep stirring at a preset temperature for a preset time to obtain an intermediate; synthesizing the intermediate and nano-metal particles to obtain an electrode catalyst; as well as The electrode catalyst is formed on the substrate.

6. The preparation method according to claim 5, characterized in that: The metal precursor solution includes at least two of a transition metal, a lanthanide rare earth element and a platinum group noble metal element, wherein the transition metal includes at least one of Mn, Cr, Zr, Fe, Co, Ni, Cu, Zn, Mo or W, and the platinum group noble metal element includes at least one of Ru, Rh, Pd, Ag, Os, Ir, Pt or Au.

7. The preparation method according to claim 4, characterized in that: Also includes: A first inducer and a second inducer are added in sequence, wherein the first inducer includes solvents such as metal acid salts, metal halides, metal sulfates and metal nitrates, the metals are selected from at least two of Mn, Cr, Fe, Co, Ni, Cu, Zn and platinum group noble metal elements, and the second inducer is selected from at least one of organic solvents such as methanol, ethanol, propanol, acetone, dimethylformamide, cyclohexane, ethyl acetate and dimethyl sulfoxide.

8. The preparation method according to claim 7, characterized in that: The (molar) ratio of the metal precursor solution, the first inducer and the second inducer is 1:1 to 1:

10.

9. The preparation method according to claim 5, characterized in that: The organic inducing agent in the electrode catalyst is selected from isophthalic acid esters, phthalates, 1,4-diazabicyclo[2.2.2]octane, triethylenediamine, 1,4-dimethylpiperazine, hexamethylenetetramine, pyromellitic acid, trimesic acid, 1,4-di(1H-pyrazol-4-yl)benzene, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracarboxylic acid, 2,4,6-tri(4-pyridyl)-1,3,5-triazine, tri(isobutylaminoethyl)amine , bis(3,5-dicarboxyphenyl)azo, biphenyl dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,6-naphthalene dicarboxylic acid, 1,4-phenylenedicarboxylic acid, 1,1,2,2-tetra(4-carboxyphenyl)ethylene, 1,3,5-tri(4-carboxyphenyl)benzene, 2-(diphenylphosphino)terephthalic acid, 2-amino-4-hydroxy-6-methylpyrimidine, 2-methylimidazole, 2-aminoterephthalic acid, terephthalic acid, fumaric acid and trioctyl trimellitate, etc.

10. The preparation method according to claim 4, characterized in that: The catalyst layer includes a first metal catalyst layer and a second metal catalyst layer.